Chomping at the Bit: A Descriptive Report on Pediatric Clenbuterol Ingestion. (June 2020) - Woolum, Jordan; Mancuso, Nicholas; Rutter, Philip W.; Baum, Regan A.; Akpunonu, Peter
Introduction: Clenbuterol hydrochloride is a selective beta-2 adrenergic agonist with uses in both humans and animals. Ingestions occurring within the United States are generally due to incidental ingestion of a veterinary product, use as a cutting agent for illicit substances, or illegal use for performance-enhancing purposes. Case Report: A four-and-a-half year-old male presented approximately two-and-a-half hours after an accidental ingestion of an unknown quantity of clenbuterol. Initial laboratory results and electrocardiogram were remarkable for hyperglycemia, hypokalemia, and hypophosphatemia, with an electrocardiogram demonstrating sinus tachycardia. Heart rate ranged from 126 to 147 beats per minute while other vitals remained within normal limits. The patient was observed for 24 hours and discharged with normalized vital signs, laboratory results, and electrocardiogram. Discussion: Clenbuterol hydrochloride is a beta-agonist with high potency, extended half-life, and bioavailability of 70% to 80%. Tachycardia occurs due to beta-1 receptor stimulation, as well as a homeostatic reflex to peripheral vasodilation. Hyperglycemia is not uncommon in exposures and intracellular shifting of potassium causes hypokalemia. Treatment is primarily supportive in nature, with hemodynamic management representing the primary focus of initial triage.